2004
DOI: 10.1111/j.1399-6576.2004.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subanaesthetic and anaesthetic doses of sevoflurane on regional cerebral blood flow in healthy volunteers. A positron emission tomographic study

Abstract: At sevoflurane concentrations at 0.7% and 2.0% a significant decrease in relative rCBF was detected in the thalamus. Interestingly, some of the most profound changes in rCBF were observed in structures related to pain processing (anterior cingulate and insula).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 40 publications
(108 reference statements)
5
51
1
Order By: Relevance
“…This increase and scalp location in the left hemisphere are consistent with previous findings in studies on opioid effects on the EEG [4,10,26]. Although the underlying mechanisms of action are not clearly understood, dominant left-side alterations in cerebral blood flow have been observed after sevoflurane administration (an anaesthetic drug) [27]. Likewise, Schlereth et al [28] found a left-hemisphere dominance in early sensory-discriminative dimensions of nociceptive pain processing (particular in left frontal operculum and adjacent dorsal insula).…”
Section: Clinical Correlations Of the Eegsupporting
confidence: 79%
“…This increase and scalp location in the left hemisphere are consistent with previous findings in studies on opioid effects on the EEG [4,10,26]. Although the underlying mechanisms of action are not clearly understood, dominant left-side alterations in cerebral blood flow have been observed after sevoflurane administration (an anaesthetic drug) [27]. Likewise, Schlereth et al [28] found a left-hemisphere dominance in early sensory-discriminative dimensions of nociceptive pain processing (particular in left frontal operculum and adjacent dorsal insula).…”
Section: Clinical Correlations Of the Eegsupporting
confidence: 79%
“…At higher sevoflurane concentrations, EEG activity is characterised by overall highamplitude, and low-peak frequency, reflecting increased delta activity [44]. As for propofol, we found increases in delta and alpha-low beta bands from awake to UN-RES and an increase in high beta from awake to SED).…”
mentioning
confidence: 48%
“…Comparison with results from other modalities, such as PET, suggests that these flows can be related to the rCBF decrease and increase observed by Schlunzen et al [6] in such brain structures involved in the wakefulness regulation as thalamus and the lingual gyrus. These arguments would support the hypothesis of Alkire et al [1] that the thalamus is the structure involved in consciousness control.…”
Section: Discussionmentioning
confidence: 96%
“…with use of PET [6] showing that the decrease in rCBF in the occipital regions (posterior, lingual gyrus, precuneus and cerebellum) was associated with rCBF increase in the insula and superior temporal cortex.…”
Section: Discussionmentioning
confidence: 99%